Sustainable side-stream management in Swedish food processing companies using external actors and biogas solutions - Hagman, Linda (Frontiers in Food Science and Technology, 2023)
Side-stream management in food processing companies has the potential to improve sustainability performance by upcycling or managing bio-residuals into high-value products. This article investigates how food processing companies manage their side-streams by studying their sustainability reports, interviewing the companies, identifying external or internal side-stream management alternatives, and qualitatively analyzing the data. By learning more about how food processing companies prefer to manage their side-streams, it becomes easier to develop ideas for further refining of bio-residuals. One of the main results is that most of the companies prefer to use external actors for side-stream management and for processing them into high-value products, rather than developing and investing in the technology themselves. The few actors investing in side-stream management themselves have long-term strategies on how to become more sustainable and circular. This study also identifies biogas solutions through anaerobic digestion to have a special role in side-stream management due to its versatile and multifunctional nature.